In situ surface stress measurement and computational analysis examining the oxygen reduction reaction on Pt and Pd. (10th January 2018) - Ha, Yeyoung; Oberst, Justin L.; Zeng, Zhenhua; Hoang, Thao T.H.; Cohen, Yair; Wetzel, David J.; Nuzzo, Ralph G.; Greeley, Jeffrey; Gewirth, Andrew A.
Abstract: Dynamic electrochemical surface stress response during the oxygen reduction reaction (ORR) on Pt and Pd cantilever electrodes in HClO4 and KOH was examined to elucidate surface binding configurations during O2 reduction electrocatalysis. Upon reduction of O2, the surface of Pt exhibits a compressive surface stress response, ΔStress, in both acid and base electrolytes due to adsorption of the ORR reactant and intermediates (O2, O, and OH). The magnitude of compressive ΔStress on Pt is greater in acid relative to base. On the other hand, the surface of Pd exhibits a negligible ΔStress in acid and a slight compressive ΔStress in base. Thus, magnitudes of the compressive ΔStress (surface expansion) during the ORR follow the order of Pt (acid) > Pt (base) > Pd (base) > Pd (acid) ∼ 0. Density functional theory (DFT) calculations of adsorbate-induced excess surface stress on Pt(111) and Pd(111) surfaces imply a greater compressive surface stress induced on Pt(111) for nearly all adsorbate geometries examined. This trend, which agrees with the experimental observations, can be correlated to a greater tensile intrinsic surface stress of Pt(111) relative to Pd(111) resulting from difference in bond strength and bulk modulus of two metals. On stepped Pt(221) and Pd(221) surfaces, both the intrinsic tensile stress of the clean surface and the adsorbate-induced excess compressive stress are significantly reduced due to the presence of less coordinated, flexible step sites. Moreover, this difference between surface stress at terrace and step sites is more pronounced on Pt, which exhibits a greater intrinsic surface stress.